The Role of Japan in the Establishment of the Siamese Modern Armed Forces during the Reign of King Chulalongkorn - Boontanondha, Thep (Journal of Letters, 2024)
The establishment of Siamese modern armed forces importantly relied on military knowledge and technologies from the Western world. As a result, Siamese armed forces sent cadets to Europe, particularly King Chulalongkorn's sons, to study military science. However, the Paknam Incident in 1894, which Siam was decisively defeated by France, made the government realize the need for rapid development of the armed forces. Furthermore, Siam recognized that relying solely on European nations limited its choices for developing the armed forces. During this time, France continued to expand its influence over territories in Southeast Asia. These factors compelled Siam to find an alternative option for developing its armed forces. Therefore, Siam decided to turn to Japan. The armed forces purchased armaments and sent cadets to study military sciences in Japan. The Siamese government also used Japan to balance power among the major nations. This policy seemingly led the European nations to doubt the increasing influence of Japan over Siam. Eventually, France conceived the idea of disarming the Siamese armed forces to ensure the sovereignty of Siam.